2023
DOI: 10.2174/1570159x20666220830115018
|View full text |Cite
|
Sign up to set email alerts
|

Secondary White Matter Injury Mediated by Neuroinflammation after Intracerebral Hemorrhage and Promising Therapeutic Strategies of Targeting the NLRP3 Inflammasome

Abstract: Intracerebral hemorrhage (ICH) is a neurological disease with high mortality and disability. Recent studies showed that white matter injury (WMI) plays an important role in motor dysfunction after ICH. WMI includes WMI proximal to the lesion and WMI distal to the lesion, such as corticospinal tract injury located at the cervical enlargement of the spinal cord after ICH. Previous studies have tended to focus only on gray matter (GM) injury after ICH, and fewer studies have paid attention to WMI, which may be on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 160 publications
0
3
0
Order By: Relevance
“…Clearance Assay. ICH mice were intravenously injected with PDA-DSeMSN@Eda, and the biological matrices including feces and urine were digested at various time points (12,24,48, and 72 h postadministration). The Si concentration was quantified by using ICP-OES analysis.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearance Assay. ICH mice were intravenously injected with PDA-DSeMSN@Eda, and the biological matrices including feces and urine were digested at various time points (12,24,48, and 72 h postadministration). The Si concentration was quantified by using ICP-OES analysis.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) is a devastating subtype of stroke with a monthly mortality rate of approximately 30–50%. , Also, only one-third of ICH survivors achieve functional independence at 12 months after ICH onset . In addition to primary brain injury, which is mainly attributed to the mechanical compression of hematoma, secondary brain injury (SBI), involving a complex array of pathophysiological processes, has been proven as a vital factor leading to neurological deterioration after ICH and a significant determinant of the adverse neurological outcome of patients. Currently, surgical clot evacuation targeting the primary injury has not yielded conclusive benefits, suggesting that SBI after ICH may represent a complementary and essential pathophysiological target. Excessive generation and accumulation of reactive oxygen species (ROS) leading to oxidative stress has been increasingly recognized as a main contributing factor of SBI. Thus, antioxidant therapy may be a promising therapeutic strategy to alleviate SBI after ICH. Edaravone (Eda), a strong free radical scavenger, has been widely used for ischemic stroke treatment. In recent years, clinical and animal experiments have demonstrated that edaravone exerts promising neuroprotective effects against ICH-induced injury. However, the therapeutic efficacy of edaravone is far from satisfaction owing to its poor water solubility, metabolic unstability, and off-target side effects .…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis, an in ammatory cell death pathway, is mediated by Nlrp3 (NOD-like receptor family pyrin domain containing 3), which forms the in ammasome complex and activates Caspase-1, leading to the release of IL-1β and IL-18 [27][28][29][30][31][32] . While Nlrp3's role in neuroin ammation and injury post-ICH is established, its direct effects on BBB disruption are less explored [33][34][35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%